Pour une approche polyphonique du journal intime - Bors, Edit (Verbum – Analecta Neolatina, 2004)
The genre of the intimate diary is a monophonic narration par excellence; nevertheless, it will be shown that even personal genres are not exempt from the presence of others. The purpose of the paper is to examine the occurrence of polyphonic marks based on some extract of young ladies' diaries collected and published by Lejeune. The analysis reaches the conclusion that others' words appear in the form of scriptural marks like quotation marks and metalinguistic comments which make it possible for the diarists to use and refuse at the same time any discourse borrowed from their social surroundings.